PEMANFAATAN MODEL PEMBELAJARAN LEVEL OF INQUIRY BERBASIS VIRTUALL LABORATORY PHET UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PESERTA DIDIK - Lumbu, Albert; Panda, Florentina Maria (JURNAL PENGABDIAN PAPUA, 2024)
The aim of the community service activity is to provide assistance to teachers in implementing the Phet virtual laboratory-based level of inquiry learning model and improve students' science process skills in using the Phet virtual laboratory- based level of inquiry learning model. The implementation of this activity will also involve the principal and science teacher at YPK Sentani Middle School, as well as students from the Physics Education study program at FKIP Cenderawasih University. The PKM activity schedule is planned for March-August 2023. Based on the results of the LKPD data analysis regarding mastery of the concept of Optical Geometry using the Level of Inquiry Learning Model with Phet Virtual Laboratory based learning media with 17 students getting a score between 81-100 and 28 students getting a score of 61-80, so that mastery of the concept of Optical Geometry using Virtual Laboratory-based learning media can be well understood by students. The results of mastering the concept of Optical Geometry obtained from student worksheets found that 38% of the total number of students had a score of 81-100, and 62% of students had a score of 61-80 with an average score of 82 so it can be concluded that the use of learning media Phet-based Virtual Laboratory can improve learning outcomes.